Intersegmental kinetics significantly impact mapping from finger musculotendon forces to fingertip forces - Qiu, D.; Lee, S. W.; Amine, M.; Kamper, D. G. (Journal of Biomechanics, 2017)
Predicting the fingertip force vector resulting from excitation of a given muscle remains a challenging but essential task in finger biomechanical modeling. While the conversion of musculotendon force to fingertip force can significantly be affected by finger posture, current techniques utilizing geometric moment arms may not capture such complex postural effects. Here, we attempted to elucidate the postural effects on the mapping between musculotendon force and fingertip force through in vitro experiments. Computer-controlled tendon loading was implemented on the 7 index finger musculotendons of 5 fresh-frozen cadaveric hands across different postures. The resulting fingertip forces/moments were used to compute the effective static moment arm (ESMA), relating tendon force to joint torque, at each joint. The ESMAs were subsequently modeled in three different manners: independent of joint angle; dependent only upon the corresponding joint angle; or dependent upon all joint angles. We found that, for the reconstruction of the fingertip force vector, the multi-joint ESMA model yielded the best outcome, both in terms of direction and magnitude of the vector (mean reconstruction error <4° in direction and <2% in the magnitude), which indicates that intersegmental force transmission through a joint is affected by the posture of neighboring joints. Interestingly, the ESMA model that considers geometric changes of individual joints, the standard model used in biomechanical stimulations, often yielded worse reconstruction results than the simple constant-value ESMA model. Our results emphasize the importance of accurate description of the multi-joint dependency of the conversion of tendon force to joint moment for proper prediction of fingertip force direction.